2016
DOI: 10.1108/jfmm-09-2014-0068
|View full text |Cite
|
Sign up to set email alerts
|

Media influence, fashion, and shopping: a gender perspective

Abstract: Purpose – Promotional media and gender have been shown to influence purchase and shopping channel choice. The purpose of this paper is to better understand the role of media influence, fashion consciousness, and fashion leadership on shopping channel choice in regard to gender. Design/methodology/approach – A survey was administered using a convenience sample of male and female students at a Southwestern University in the USA. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 40 publications
4
47
1
9
Order By: Relevance
“…In paper by Hansen and Jensen (2009), it was found that Internet users most often looked for information about clothes, footwear and broadly defined accessories. Similar results have been obtained in recent studies by Geissinger and Laurell (2016) and Shephard et al (2016). The products most often researched by consumers on the Internet are definitely more expensive.…”
Section: Types Of Products Which Users Exchange Information About Viasupporting
confidence: 89%
“…In paper by Hansen and Jensen (2009), it was found that Internet users most often looked for information about clothes, footwear and broadly defined accessories. Similar results have been obtained in recent studies by Geissinger and Laurell (2016) and Shephard et al (2016). The products most often researched by consumers on the Internet are definitely more expensive.…”
Section: Types Of Products Which Users Exchange Information About Viasupporting
confidence: 89%
“…Another research explored variables influencing media usage patterns among different genders. The results have also shown that behavior of men and woman in consuming information from media, and especially new media, differs (Shephard et al, 2016). However, the scope of research focusing on the difference in customer segments remains limited.…”
Section: Relevance Of the Theory Of Generationsmentioning
confidence: 99%
“…Influenciadas pela profissão, todas as mulheres entrevistadas observam o tecido, o corte, a composição e o acabamento da peça para adquiri-la. Independente do estilo que optam por usar, a peça deve vestir bem, favorecer quem a usa de modo a atender os desejos de suas consumidoras (Shephard et al, 2016). É neste universo que se encontram os aspectos subjetivos de escolha.…”
Section: Critérios De Escolha Na Aquisição De Roupasunclassified
“…Assim, o objetivo do presente artigo é analisar o consumo de roupas realizado por esses profissionais, mais especificamente, por empresárias, uma vez que as mulheres são descritas por Barletta (2006) como as grandes personagens da sociedade de consumo. As mulheres utilizam suas roupas como aspectos da imagem corporal, representando uma parte crucial do gerenciamento de aparência feminina (Shephard, Pookulangara, Kinley & Josiam, 2016). As preferências para a escolha de vestimentas, as formas de aquisição, uso e descarte das mesmas e o valor atribuído a elas demonstrando o simbolismo infligido nas roupas foram as questões norteadoras do presente artigo.…”
Section: Introductionunclassified